Nine Pfizer/IOC Olympic research projects in progress during Olympic Winter Games in Salt Lake City (2000)
The International Olympic Committee (IOC) and Pfizer are conducting nine Olympic research projects at the 2002 Olympic Winter Games in Salt Lake City. This year marks the first time that research conducted on athletes in conjunction with the Olympic Games will encompass health and nutrition in addition to natural performance improvement and injury reduction through biomechanics research.